Hubungan antara kepuasan kerja dengan persepsi terhadap prestasi kerja di sektor perkhidmatan awam beruniform : satu tinjauan di Jabatan Pengangkutan Jalan Malaysia di Sarawak - Hamidah, Ishak (Universiti Malaysia Sarawak, (UNIMAS), 2004)
The purpose of this study is to examine the correlation between the five aspects of job satisfaction and perception towards job performance among officers of Malaysian Road Transport Department in Sarawak. The considered aspects of job satisfaction in this study are the work condition, salary condition, raised opportunities, supervising style and colleague. The sample of this study is 60 JPJ officers in Sarawak who work in different department and branches. The result of this study is analyzed using descriptive and inferential statistic. Based on the mean analysis done, it is found that respondents are only satisfied with the Colleagues and supervising style aspects. Other than that, the mean analysis shows that respondent are of the perception that their job performance are in a high level. To test the hypotheses, Pearson Correlation test is used. The result shows that there is no significant relationship between the five aspects of job satisfaction and perception towards job performance.